2016
DOI: 10.1186/s12864-016-3104-5
|View full text |Cite
|
Sign up to set email alerts
|

A performance study of the impact of recombination on species tree analysis

Abstract: BackgroundThe most widely used state-of-the-art methods for reconstructing species phylogenies from genomic sequence data assume that sampled loci are identically and independently distributed. In principle, free recombination between loci and a lack of intra-locus recombination are necessary to satisfy this assumption. Few studies have quantified the practical impact of recombination on species tree inference methods, and even fewer have used genomic sequence data for this purpose. One prominent exception is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…Some studies (e.g. Gatesy & Springer, ; Springer & Gatesy, ) argue that recombination might affect coalescent‐based phylogenetic analyses, but simulation studies have shown that methods for species tree inference may be largely robust to intra‐locus recombination (Lanier & Knowles, ; Wang & Liu, ), and a recent empirical study showed that, despite a large amount of recombinant loci (~ 42%), ASTRAL‐II still recovered the same topology with these loci included or excluded from species tree analyses (Folk et al ., ). With respect to our ASTRAL‐II analyses, the only difference with and without recombinant loci is again in the placement of the Orbiculate clade.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies (e.g. Gatesy & Springer, ; Springer & Gatesy, ) argue that recombination might affect coalescent‐based phylogenetic analyses, but simulation studies have shown that methods for species tree inference may be largely robust to intra‐locus recombination (Lanier & Knowles, ; Wang & Liu, ), and a recent empirical study showed that, despite a large amount of recombinant loci (~ 42%), ASTRAL‐II still recovered the same topology with these loci included or excluded from species tree analyses (Folk et al ., ). With respect to our ASTRAL‐II analyses, the only difference with and without recombinant loci is again in the placement of the Orbiculate clade.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include statistical inference of species trees under non-i.i.d. models of sequence evolution (Thorne et al, 1992;Wang and Liu, 2016), machine learning using temporal models (Breiman, 1996), and many, many more -far too many to list here. Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…Also, recombination breakpoints and ILS that are associated with increasingly divergent taxa will exhibit higher levels of homoplasy. Still, coalescence analyses will be compromised if the critical issue of c-gene boundaries is simply ignored [ 21 ]. One strategy may be to search for recombination breakpoints with small subsets of taxa that are associated with individual coalescent events (e.g., human-chimp-gorilla or three species of Equus ) and then to combine these together to produce a c-gene map for the full set of taxa.…”
Section: Criticisms Of the Recombination Ratchetmentioning
confidence: 99%
“…In another relevant simulation study, Wang and Liu [ 21 ] compared data-driven methods for detecting recombination and reported that pipelines that use direct analysis of the data to explicitly infer breakpoints and delineate c-genes (‘recombination-free intervals’) result in greater species tree accuracy with the summary coalescence method ASTRAL II relative to pipelines that pre-process loci into intervals of a given length based on independent estimates of linkage disequilibrium decay. Wang and Liu’s [ 21 ] explicit recombination approach was limited to detecting recombination breakpoints with the four-gamete test (FGT) [ 59 ]. The FGT assumes the infinite sites model, so all violations of the four-gametes rule are interpreted as recombination.…”
Section: Simulations Of Coalescence With Recombinationmentioning
confidence: 99%
See 1 more Smart Citation